Efeitos agudos do extracto rico em CDB na sensibilidade ao contraste no transtorno do espectro autista: um estudo de caso - Oliveira, Amanda Gleiciane de Lima (2023)
The extract rich in Cannabidiol (CBD) has been associated with improving behavioral symptoms, cognitive, and sensory functions in Autism Spectrum Disorder (ASD). However, studies on the effects of CBD on the vision of people with ASD are still scarce. Thus, this case study describes the effects of CBD on contrast sensitivity (CS) in a 14-year-old adolescent, disclosed with ASD, level 1 support. The intervention took place over four weeks, with daily administration of 10 drops of oil enriched with CBD, divided into two doses of 4,415 mg. The participant performed pre- and post-intervention assessments. The Childhood Autism Scale Rating - CARS and the Socially Savvy Checklist were used to evaluate, respectively, behaviors associated with ASD and social skills. SC was measured using vertical sinusoidal degrees for the frequency range of 0.2 to 14.5 cycles per degree (cpg). There were no side effects of the intervention over four weeks. There was an increase in SC for all spatial frequencies, except 14.5 cpg, being more pronounced at spatial frequencies of 0.6, 3.1, and 6.2 cpg. Furthermore, a reduction of 9 points in the total CARS scale score was observed. Despite limitations, such as the small sample size and the absence of other sensory-cognitive measures, this report is important for several fields of study. Overall, the results represent relevant guidance in investigating the therapeutic potential of CBD in ASD.